(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2024)
Introduction: Hepatoid adenocarcinoma (HAC) of the stomach is a rare tumor with limited clinical data. This study aims to study the clinicopathological and radiological features of hepatoid adenocarcinoma of the stomach and its two subtypes. Materials and methods: Histopathologically confirmed 39 gastric hepatoid adenocarcinoma cases (16 pure hepatoid carcinomas and 23 mixed hepatoid carcinomas from 30 males and 9 females) with mean age of 60 years (36 to 78 year) were included in this ethical committee approved retrospective study. Clinicopathological data was extracted from the system. Two radiologists evaluated the radiological features. Results: The serum Alfa-fetoprotein was higher in the pure group (p=0.008). Pure hepatoid carcinoma group was larger than the mixed group, with average tumor size of 5.75± 2.13 cm Vs 4.27± 1.48 (p=0.02). Pure hepatoid carcinoma group had a substantial association with positive AFP staining of 57.10% Vs 9.10 % in mixed group (p=0.005). On CT, HAC showed significant eccentric wall thickening (p<0.001) and a higher number (74.36%) of tumor in pylorus of the stomach (p<0.001). Liver metastasis and tumor thrombosis were significantly negatively associated with HAC. A single case of tumor thrombus was seen in the pure group. All HAC enhanced heterogeneously and occupied extremes of T and N stage. Conclusions: HAC of stomach mainly affects middle to older aged males. On CT, it enhances heterogeneously with eccentric wall thickening in pylorus of the stomach. Pure hepatoid carcinoma differs from mixed hepatoid carcinoma only in terms of its large tumor size, high serum AFP level, and high positive AFP staining.